Development of Educational Videos Using the Animaker Application with Interactive Quizzes Using the Wordwall Application in Junior High Schools - Rahman, Ummu Fitrah Widia; Sari, Milya; Masyhudi, Fauza; Hidayati, Hidayati; Eliza, Rivdya (STIT Ahlussunnah Bukittinggi, 2025)
This research aimsto develop learning videos with interactive quizzes on SKI subjects at MTsN.This research uses the method R&D (Research and Development). The model used is a 4D model. This model consists of four stages, namely: Stage Define(definition), this stage involves needs analysis, learning media analysis, CP, TP and ATP analysis, and material analysis. Design (design), at this stage the steps taken are designing the material and illustrations, makingflowchart, programing and making learning video products. Level Development (development), at this stage, validation is carried out by material, media, and language experts. After that, practicality testing is carried out by educators and students with two small group and large group trials.Analysis resultsshows that the development of learning videos and interactive quizzes has met the criteria of being very valid and very practical so that it is worthy of being developed. Research resultThe results showed that the learning video with interactive quizzes met the criteria for valid, practical, and effective media. Expert validation results indicated that the learning video with interactive quizzes was highly valid in terms of material/content, construction/media, and language, with an overall score of 94.93%. The practicality test results showed that the learning video with interactive quizzes was highly practical, with a score of 95.83. This means that the developed product is very practical for use in the learning process.